Global concern for children's rights : the World Congress against sexual exploitation. - MAHLER, Karen (1997)
Notes that despite the long list of international legal instruments addressing sexual exploitation and the related issues of trafficking, forced labour, slavery-like practices and discrimination, the sexual exploitation of children appears to be a worldwide phenomenon. Identifies the roots of the problem as being gender discrimination and inequality, labour migration and trafficking, and child labour. Discusses the World Congress Agenda for Action which stresses the development and enforcement of laws to specifically prohibit the commercial sexual exploitation of children, to penalize those responsible for exploitation at every level of their involvement and to protect exploited children from being further victimised through improper or insensitive law enforcement.